Irrigation History in Central Nepal: The Interface between Agriculture and Technology (Water Nepal, 2004)
This paper summarises agricultural data and water distribution techniques collected in Gulmi District to propose a hypothesis about irrigation history in central Nepal. It places irrigation in its socio-economic context and shows how changes in the farming system, which took place in the beginning of the 20th century had major impact on water management and water division technique. All irrigation systems built during this period required major construction work and defined rights to a share of water. The changes intensified agricultural succession and the individualisation of space management. The story of Aslewacaur Canal demonstrates that the reasons for establishing of a farmer irrigation system were not simply economic.Water Nepal Vol.11(2) 2004 pp.19-43